2019
DOI: 10.1161/atvbaha.118.310956
|View full text |Cite
|
Sign up to set email alerts
|

Therapies for Thoracic Aortic Aneurysms and Acute Aortic Dissections

Abstract: Thoracic aortic aneurysms that progress to acute aortic dissections are often fatal. Thoracic aneurysms have been managed with treatment with β-adrenergic blocking agents (β-blockers) and routine surveillance imaging, followed by surgical repair of the aneurysm when the risk of dissection exceeds the risk for repair. Thus, there is a window to initiate therapies to slow aortic enlargement and delay or ideally negate the need for surgical repair of the aneurysm to prevent a dissection. Mouse models of Marfan sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 98 publications
(121 reference statements)
1
109
0
1
Order By: Relevance
“…Based on the relatively high expression of their respective targets in the aorta of MFS mice, this shorter list of top-ranked drugs was narrowed down to the steroid fludrocortisone and the muscle relaxant baclofen ( Figure 2B). However, fludrocortisone was excluded from further analyses because of its potential to induce iatrogenic arterial hypertension, the major risk factor for thoracic aortic disease (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the relatively high expression of their respective targets in the aorta of MFS mice, this shorter list of top-ranked drugs was narrowed down to the steroid fludrocortisone and the muscle relaxant baclofen ( Figure 2B). However, fludrocortisone was excluded from further analyses because of its potential to induce iatrogenic arterial hypertension, the major risk factor for thoracic aortic disease (14).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies of MFS mice with nondissecting TAA (Fbn1 C1039G/+ mice) have correlated aneurysm onset and progression with increased TGF-β signaling in the media stimulated by improper angiotensin II (AngII) type I receptor (AT1r) activity (6,7). More recent findings indicate a more complex disease mechanism involving the gradual stratification of stress-stimulated interactions among different cell types and multiple regulatory pathways, of which the AT1r and TGF-β signaling pathways are a critical subset (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…It was originally demonstrated more than 70 years ago when turkeys eating sweet pea seed, Lathyrus odoratus, which contains the lysis oxidase inhibitor, B-aminopropionitrile, die of acute aortic dissections. The beta blocker propranolol was found to decrease deaths from dissection in B-aminopropionitrile fed turkeys [40][41][42][43]. Beta-blockers such as propranolol benefit the aortic wall through negative inotropic and chronotropic effects.…”
Section: Medical Therapymentioning
confidence: 99%
“…AAD patients with a time interval of ≤14 days from the onset of symptoms to hospital admission were included in the present study. Exclusion criteria included (1) uncompleted LDH tests, (2) prior history of a malignant tumor or liver cirrhosis, (3) diagnosis with pregnancy, and (4) presence of AAD for more than 14 days.…”
Section: Study Design and Settingsmentioning
confidence: 99%
“…Acute aortic dissection (AAD) is a catastrophic aortic disease with high mortality and morbidity that requires immediate diagnosis and treatment [1,2]. From 1% to 2% of patients with AAD die per hour for the first 24∼48 hours [3]. Previous studies have found that many noninvasive markers, such as CRP and D-dimer, are considered to be associated with AAD severity [4,5].…”
Section: Introductionmentioning
confidence: 99%